Can the presence of foreign investment affect the capital structure of domestic firms? - Anwar, Sajid; Sun, Sizhong (Journal of Corporate Finance, 2015)
Using a simple theoretical model, this paper argues that an increase in foreign presence, which refers to the level of foreign investment in a given domestic firm, can affect the leverage of domestic firms. We apply the model to explore the link between foreign presence and leverage with firm level panel data from China. The empirical estimation, using instrumental variable Tobit regression, reveals that, in overall terms, the impact of foreign presence on the leverage of domestic firms in China's manufacturing sector is negative. We find that the negative impact on the leverage of privately owned firms is large relative to state-owned firms. Furthermore, we find that the impact of foreign presence on leverage varies from industry to industry, which is consistent with the presence of heterogeneity in the productivity spillover effect.